ความสัมพันธ์ระหว่างการตอบสนองต่ออาการ และระยะเวลาการมาถึงโรงพยาบาลของผู้ป่วยโรคหลอดเลือดสมองเฉียบพลัน Relationships among Response to Symptoms and Hospital Arrival Time of Acute Stroke Patients - Potisopha, Wiphawadee (วารสารพยาบาลศาสตร์และสุขภาพ, 2015)
บทคัดย่อ การวิจัยเชิงความสัมพันธ์ มีวัตถุประสงค์เพื่อศึกษาความสัมพันธ์ระหว่างการตอบสนองต่ออาการ กับระยะเวลาการมาถึงโรงพยาบาลของผู้ป่วยโรคหลอดเลือดสมองเฉียบพลัน จำนวน 85 ราย ที่เข้ารับการรักษาในหน่วยโรคหลอดเลือดสมอง โรงพยาบาลระดับตติยภูมิในจังหวัดขอนแก่น วิเคราะห์ข้อมูลโดยใช้สถิติเชิงบรรยาย สัมประสิทธิ์สหสัมพันธ์สเปียร์แมนและไคสแควส์ ผลการศึกษาพบค่ามัธยฐานของระยะเวลาการมาถึงโรงพยาบาลเท่ากับ 259 นาที การตอบสนองต่ออาการที่มีความสัมพันธ์กับระยะเวลาการมาถึงโรงพยาบาล ได้แก่ การรับรู้ความสามารถในการควบคุมอาการ (p < .01) การรับรู้ความรุนแรงของอาการ (p < .01) ความวิตกกังวล (p < .05) การตอบสนองต่ออาการด้านการตอบสนองของบุคคลที่เกี่ยวข้อง และการตอบสนองทางพฤติกรรม (p < .001) ผลการศึกษาแสดงให้เห็นว่าการตอบสนองต่ออาการโรคหลอดเลือดสมองมีความสัมพันธ์กับระยะเวลาการมาโรงพยาบาล บุคลากรทางสุขภาพจึงควรพัฒนาแนวทางการให้ข้อมูลเรื่องการตอบสนองต่ออาการที่เหมาะสมแก่ผู้ป่วยโรคหลอดเลือดสมองเฉียบพลันเพื่อเพิ่มศักยภาพในการตอบสนองที่เหมาะสมและลดระยะเวลาการมาถึงโรงพยาบาล Abstract The correlational research aimed to study the relationships among response to symptoms, mode of transportation, and hospital arrival time of acute stroke patients. The sample consisted of 85 acute stroke patients that were admitted at the stroke unit in tertiary care hospitals in KhonKaen province. Descriptive statistics, Spearman Rank correlation, and Chi-square test were utilized in data analysis. The results revealed that the median of hospital arrival time was 259 minutes. The variables that had a significant relationship with hospital arrival time were perceived ability to control symptoms (p < .01), perceived severity of symptoms (p < .01), anxiety (p < .05), bystander response and first behavioral response of participants to symptoms (p < .001). The findings indicated that there was relationship between response to stroke symptoms and hospital arrival time. Thus, healthcare providers should develop informational guidelines to promote appropriate response to symptoms of acute stroke patients in order to improve appropriate response and decrease hospital arrival time.